Optimizing the retention and leaching of potassium of Tropical mineral acid soils with application of charcoal and Sago bark ash - Paramisparam, Puvan; Ahmed, Osumanu Haruna; Omar, Latifah; Johan, Prisca Divra; Hamidi, Nur Hidayah; Ch’ng, Huck Ywih; Musah, Adiza Alhassan (Malaysian Society of Soil Science, 2024)
Potassium (K) is a macronutrient required by plants for energy production, enzyme activation, formation of cell wall, production of protein, and photosynthesis. However, its availability is compromised because of leaching. In mineral acid soils such as Ultisols and Oxisols, K in the soil solution is prone to leaching because of high rainfall and abundance of kaolinite clay minerals and sequioxides. As a result, these soils have low cation exchange capacity (CEC) but aluminium (Al) and iron (Fe) predominates. This problem has steered the attention to the application of amendments to increase K retention in such soils. The highly negative-charged sites of charcoal and sago bark ash can increase CEC to enhance K+ retention. Moreover, the alkalinity of these amendments can improve mineral acid soil pH to suppress Al and Fe toxicity in addition to improving K availability soils. The objective of this study was to optimize the retention to reduce leaching of K in a tropical mineral acid soil (Typic Paleudults) through co-application of charcoal and sago bark ash. The proportions of charcoal and sago bark ash used in this present study were varied at 20, 40, 60, 80, and 100, but the MOP was fixed at 100 of the recommended rate. Selected soil chemical properties before and after the leaching study were determined using standard procedures. Results revealed that increasing rates of charcoal improved soil CEC, (total carbon) TC, and exchangeable K at 30 days leaching. Leaching of K was relatively high in the soil with chemical fertilizers compared with the soils with charcoal and sago bark ash despite the K source for the former coming solely from MOP. Although the increasing rate of sago bark ash had minimal effect on the soil exchangeable K, the ability of the sago bark ash to activate the functional groups of the charcoal is important to further increase maximum K buffering capacity. Therefore, the findings of this present study suggest that the optimum rates of charcoal and sago bark ash to reduce K leaching in mineral acid soils are 60 charcoal with 60 sago bark ash (6 t ha−1 charcoal and 3 t ha−1 sago bark ash) and 80 charcoal with 40 sago bark ash (8 t ha−1 charcoal and 2 t ha−1 sago bark ash), because these rates improved soil exchangeable K+, TC and CEC significantly, in addition minimizing soil exchangeable acidity at 30 days of leaching.